Cominternismo intelectual: Representaciones, redes y prácticas político-culturales en América Central, 1921-1933 - Melgar Bao, Ricardo (Revista Complutense de Historia de América, 2010)
The article deals with a novel theme in the intellectual history of Central America, related to the formation of the communist parties’ regional intellectual networks, between 1921 and 1933. The article delineates the profile of the Comintern intellectual committed to social realities, and the projection of these intellectuals in education, syndicalist life and the practice of politics in Central America.
Keywords: Intellectuals; Intellectual Capital; Cominternism; Networks; Political and Cultural Representations and Practice; Central America; 20th Century